2010
DOI: 10.1111/j.1600-0714.2010.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical photodynamic therapy is very effective for oral verrucous hyperplasia and oral erythroleukoplakia

Abstract: This study indicates that the laser light-mediated topical ALA-PDT is also very effective for OVH and OEL lesions. Therefore, we suggest that topical ALA-PDT using either the LED or laser light may serve as the first-line treatment of choice for OVH and OEL lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 18 publications
4
78
1
3
Order By: Relevance
“…In previous studies, McGillis and Fein 15 and Rivard and Ozog 16 have also applied ALA for 30 minutes before illumination and exposition to light for 10 minutes in 3 fractions. In most of the previous studies the light sources used were lasers at 635 nm, Kübler et al, 17 Fan et al, 18 Kubler et al, 19 Sieron et al, 20 Sieroń et al, 21 Tsai et al, 22 Chen et al, 23 Lin et al, 24 and 585 nm, Franco, 25 Shafirstein et al 26 But, because of their bulkiness and high cost, we have chosen LED at 420 nm, like McGillis and Fein, 15 Rivard and Ozog, 16 Ericson et al, 27 Jerjes et al, 28 as it is cheaper, convenient, safe and easy to use in the treatment of OL and OLP. In the present study, 12 OL lesions were treated with 5-ALA mediated PDT, among which 2 (16.7%) showed complete response, 8 (66.67%) partial response and 2 (16.7%) no response.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, McGillis and Fein 15 and Rivard and Ozog 16 have also applied ALA for 30 minutes before illumination and exposition to light for 10 minutes in 3 fractions. In most of the previous studies the light sources used were lasers at 635 nm, Kübler et al, 17 Fan et al, 18 Kubler et al, 19 Sieron et al, 20 Sieroń et al, 21 Tsai et al, 22 Chen et al, 23 Lin et al, 24 and 585 nm, Franco, 25 Shafirstein et al 26 But, because of their bulkiness and high cost, we have chosen LED at 420 nm, like McGillis and Fein, 15 Rivard and Ozog, 16 Ericson et al, 27 Jerjes et al, 28 as it is cheaper, convenient, safe and easy to use in the treatment of OL and OLP. In the present study, 12 OL lesions were treated with 5-ALA mediated PDT, among which 2 (16.7%) showed complete response, 8 (66.67%) partial response and 2 (16.7%) no response.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al [39] indicated that the laser light-mediated topical ALA-PDT is also very effective for oral verrucous hyperplasia (OVH) and oral erythroleukoplakia lesions (OEL). Therefore, they suggested that topical ALA-PDT using either LED or laser light may serve as the first-line treatment of choice for OVH and OEL lesions.…”
Section: Diagnosis and Treatment Of Premalign And Malign Lesions Of Hmentioning
confidence: 99%
“…The total number of subjects ranged between 5 patients and 147 individuals. Seven studies [9,15,16,[20][21][22][23] reported the mean age of study participants, which was between 51 years and 62.2 years (age range 30-98 years). Nine studies [9,15,16,[18][19][20][21][22][23] reported the gender of subjects, in which the number of female participants ranged between 0 and 65 individuals.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
“…Twenty-three studies, which did not fulfill the eligibility criteria, were excluded (Appendix A). In total, 13 studies [9,[15][16][17][18][19][20][21][22][23][24][25][26] were included and processed for data extraction. The pattern of the present study was customized to mainly summarize the relevant information.…”
Section: Search Strategymentioning
confidence: 99%